2017
DOI: 10.9734/cjast/2017/35186
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Character Association in Barley (Hordeum vulgare L.) Genotypes for Yield and Yield Related Traits

Abstract: One hundred and seventy barley germplasm lines (101 two rowed and 69 six rowed) and three standard checks (BH393 six rowed, BH946 six rowed and BH885 two rowed) were evaluated for ten quantitative traits using augmented block design consisting of 10 complete blocks during rabi season of 2014-2015 at Wheat and Barley section research farm,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…According to Tinker et al (1996) Estimates of broad-sense heritability for barley grain yield, varied considerably in the literature, probably due to differences in the type of genetic material and the environments where the studies were performed. Some authors reported high or moderate values (Addisu et al, 2015;Akgün, 2016;Sunil and Khan, 2017) while others found low estimates (Ahmadi et al, 2016) for this trait.…”
Section: Variance Components and Genetic Parametersmentioning
confidence: 95%
“…According to Tinker et al (1996) Estimates of broad-sense heritability for barley grain yield, varied considerably in the literature, probably due to differences in the type of genetic material and the environments where the studies were performed. Some authors reported high or moderate values (Addisu et al, 2015;Akgün, 2016;Sunil and Khan, 2017) while others found low estimates (Ahmadi et al, 2016) for this trait.…”
Section: Variance Components and Genetic Parametersmentioning
confidence: 95%
“…The genetic variation between cultivars of barley and their related wild species easily gives way to use for the hybridization process in plant breeding. Barley has become a model plant experimental system for much scientific research around the world [11][12][13][14][15][16][17][18].…”
mentioning
confidence: 99%